2015
DOI: 10.1093/intqhc/mzu103
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in primary health care settings in the Eastern Mediterranean region: a systematic review of the literature

Abstract: These findings highlight gaps in evidence on quality in PHC in the EMR; such evidence is key for decision-making. Researchers and policy-makers should address these gaps to generate contextualized information and knowledge that ensures relevance and targeted high-impact interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 117 publications
1
29
0
Order By: Relevance
“…There is a wide range of available resources and health care expenditure for individuals with diabetes in the region (7). Moreover, quality of care is a major concern in some countries of the region (40). In general, however, there is an underinvestment in diabetes care, even in the high-income countries of the EMR compared with high-income Western countries (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide range of available resources and health care expenditure for individuals with diabetes in the region (7). Moreover, quality of care is a major concern in some countries of the region (40). In general, however, there is an underinvestment in diabetes care, even in the high-income countries of the EMR compared with high-income Western countries (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, findings of a study conducted in 2015 showed that there were gaps in the evidence on quality in primary care in the EMR region [ 7 ]. Another primary care - focused research revealed no major difference in compliance with accreditation standards between health services that went for accreditation and their counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the EMR, WHO has its own Index Medicus for the Eastern Mediterranean Region (IMEMR), which includes some 600 journals produced in the Region, some of which, but not all, are included in PubMed. Subsequent similar studies should include such important database (20,21).…”
Section: Discussionmentioning
confidence: 99%